High replacement of fishmeal by Chlorella meal affects intestinal microbiota and the potential metabolic function in largemouth bass (Micropterus salmoides) - Zhang, Zhimin; Xi, Longwei; Liu, Haokun; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Han, Dong; Xie, Shouqi (Frontiers in Microbiology, 2022)
Microalgae have beneficial effects on the performance of fish as additives and they are becoming a promising alternative to fishmeal as macronutrient ingredients. However, the impact on the fish intestinal microbiome and the function, caused by microalgae as protein sources in diets, remains unclear. This study aimed to determine the composition and potential function of the intestinal microbial community of largemouth bass (Micropterus salmoides) fed diets at five replacement levels (0%, 25%, 50%, 75% and 100%) of fishmeal by Chlorella meal in a basal diet (400 g kg-1) after 8 weeks. The results showed significant decreases in unique amplicon sequence variants (ASVs) in the intestine at the higher levels of fishmeal replacement. At 50% of fishmeal replacement, dietary inclusions of Chlorella meal had no impact on species richness and Shannon diversity and the community structure of the intestinal microbiota. However, high levels of fishmeal replacement (75% and 100%) significantly induced intestinal community disturbance and diversity loss in largemouth bass. Responding to the high fishmeal replacement level, the dominant genus Cetobacterium and Pleslomonas sharply increased and several taxa from Lactobacillus decreased significantly. Functional data predicted by PICRUSt revealed that nutrition-related metabolism was dominant in the intestinal microbiota of fish fed all the five diets, although some potential functions, particularly amino acid and lipid metabolisms, and energy metabolism, were upregulated firstly, and then downregulated in fish fed diets with the increase of dietary Chlorella meal. Meanwhile, certain pathways were not enriched in intestinal microbiome until up to 75% of fishmeal replacement, such as carbohydrate metabolism, and cofactors and vitamins metabolism. To conclude, this study reveals that fishmeal replacement (50%) by Chlorella meal at the level of 237 g kg-1 in diets is feasible for largemouth bass without impairing the microbiome structure and the metabolism function, providing an alternative strategy for evaluating the possibility of fishmeal replacement by microalgae in aquafeeds.